PENGARUH NILAI PELANGGAN TERHADAP KINERJA PEMASARAN PADA PETANI KARET RAKYAT DI KECAMATAN KUANTAN MUDIK KABUPATEN KUANTAN SINGINGI (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2022)
The success of customer value can affect the marketing performance of rubber. The research was conducted in Kuantan Mudik District, Kuantan Singingi Regency, Riau. The purpose of this study was to determine the effect of customer value on emotional value, social value, quality value, and price value on smallholder rubber farmers. The population in this study were 205 farmers, the sample was taken 15% of the population of 31 farmers selected by simple random sampling technique. Analysis of the data used is multiple linear regression analysis with SPSS application. The results of the study explain sig.t value for X1 is 0.003, sig.t value of X2 is 0.014, sig. t value of X3 is 0.021 which is smaller than the 0.05 level of significance. This means that X1, X2, and X3 partially have a significant effect marketing performance. While sig t value of X4 is 0.216 which is greater than the significant level, means price value partially has no significant effect marketing performance. f-test results sig.f value of 0.000 is smaller than the significant level of 0.05, meaning that the customer value seen from the emotional, social, quality, and price values simultaneously has a significant effect on increasing marketing performance.